Development and validation of quantitative thin layer chromatographic technique for determination of total aflatoxins in poultry feed and food grains without sample clean-up (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The purpose of this work is to develop and validate an appropriate solvent solution and quantitative thin layer chromatography (TLC) method for determining the aflatoxins content of chicken feeds and dietary grains.  Materials and Methods: To obtain the optimal mobile phase, samples were extracted with methanol/water (3:1) + 5% sodium chloride and partitioned using several solvent systems using preparative TLC. Camag TLC scanner 3 was used to scan the TLC plates at 366 nm and quantify them using JustTLC software. The method was tested for linearity, specificity, accuracy, precision, sensitivity, and robustness in accordance with ICH recommendations, and then utilized to screen 132 Nigerian poultry/food samples for total aflatoxins (TAFs).  Results: The best separation of aflatoxins was achieved using acetonitrile and dichloromethane (3:17) mobile phase over an average run time of 45 min, resulting in linear calibration curves (R2 > 0.99) in the concentration range limit of quantitation (LoQ) to 50 ng/spot with a limit of detection of